Understanding smart sensors - Frank, Randy (Artech House sensors library., 2000)
Here is a complete, authoritative summary of the latest applications and developments impacting smart sensors in a single volume, now updated to reflect IEEE 1451.2 smart sensor standards. Utilizing the latest in smart sensor, microelectromechanical systems (MEMS) and microelectronic research and development, you get the technical and practical information you need keep your designs and products on the cutting edge. Plus, you see how advances in fuzzy logic and neural networks continue to determine the direction of smart sensor development.